2015
DOI: 10.1590/1414-431x20154459
|View full text |Cite
|
Sign up to set email alerts
|

Low-level red laser therapy alters effects of ultraviolet C radiation on Escherichia coli cells

Abstract: Low-level lasers are used at low power densities and doses according to clinical protocols supplied with laser devices or based on professional practice. Although use of these lasers is increasing in many countries, the molecular mechanisms involved in effects of low-level lasers, mainly on DNA, are controversial. In this study, we evaluated the effects of low-level red lasers on survival, filamentation, and morphology of Escherichia colicells that were exposed to ultraviolet C (UVC) radiation. Exponential and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…It was suggested that LLLT might promote changes in the cellular redox state, playing an important role in sustaining cellular activities, and induce photobiostimlative processes [64]. In addition to the above, pre-exposure of PBM had a protective effect against many external agents such as hydrogen peroxide, H 2 O 2 , and UV radiation [65,66]. There is an evolutionary standpoint confirm that NIR pre-exposure protect cells from the hazard impacts of UV exposure, and the re-exposure for NIR radiation could be important for protection maintenance [67,68]…”
Section: Optical Sources and Biological Interactionmentioning
confidence: 99%
“…It was suggested that LLLT might promote changes in the cellular redox state, playing an important role in sustaining cellular activities, and induce photobiostimlative processes [64]. In addition to the above, pre-exposure of PBM had a protective effect against many external agents such as hydrogen peroxide, H 2 O 2 , and UV radiation [65,66]. There is an evolutionary standpoint confirm that NIR pre-exposure protect cells from the hazard impacts of UV exposure, and the re-exposure for NIR radiation could be important for protection maintenance [67,68]…”
Section: Optical Sources and Biological Interactionmentioning
confidence: 99%
“…coli cultures previously exposed to a red laser, but this effect seems more evident in these cultures (figure 2). In fact, data in others studies have demonstrated that laser-induced effects are dependent on the growth phase in E. coli cultures [12,22,23]. These results indicate that, at least in wild type cultures, laserinduced effects on cells submitted to heat stress are dependent on laser wavelength, which is different than the laser-induced effects on cells submitted to hyposmotic [8] and hyperosmotic stress [9].…”
Section: Discussionmentioning
confidence: 82%
“…However, there are few studies comparing laser-induced effects on biological systems on physiological with non physiological (stressful) conditions [8,9]. Also, genetic characteristics' influence on the effects of these lasers on cells and the participation of DNA repair mechanisms on laser-induced effects has been reported more recently [10][11][12], but this is still controversial, although some data have suggested that these lasers induce sublethal DNA lesions by free radicals generation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been suggested that LLLT may promote changes in the cell's redox state, playing an important role in ion homeostasis and consequently in cellular activity and induce photobiostimulation processes. Besides that, preexposure of PBM has a protective effect against many external agents, such as hydrogen peroxide (H 2 O 2 ) and UV radiation [124,125].…”
Section: Photobiomodulationmentioning
confidence: 99%